2015
DOI: 10.1534/genetics.115.179978
|View full text |Cite
|
Sign up to set email alerts
|

Do Molecular Markers Inform About Pleiotropy?

Abstract: The availability of dense panels of common single-nucleotide polymorphisms and sequence variants has facilitated the study of statistical features of the genetic architecture of complex traits and diseases via whole-genome regressions (WGRs). At the onset, traits were analyzed trait by trait, but recently, WGRs have been extended for analysis of several traits jointly. The expectation is that such an approach would offer insight into mechanisms that cause trait associations, such as pleiotropy. We demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 17 publications
1
55
0
Order By: Relevance
“…It is also important to note that a genetic correlation does not always indicate that a pair of phenotypes has a shared mechanism, as it is possible that SNPs used to compute the correlations may be simultaneously tagging disparate causative genetic variants. 49 Finally, these analyses were limited to subjects of European ancestry, as the numbers of subjects of other ancestries was insufficient for analysis. Further validation of this approach in other ancestral groups is needed.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to note that a genetic correlation does not always indicate that a pair of phenotypes has a shared mechanism, as it is possible that SNPs used to compute the correlations may be simultaneously tagging disparate causative genetic variants. 49 Finally, these analyses were limited to subjects of European ancestry, as the numbers of subjects of other ancestries was insufficient for analysis. Further validation of this approach in other ancestral groups is needed.…”
Section: Discussionmentioning
confidence: 99%
“…By evaluating power performance, it is shown that it can be advantageous to perform the proposed pleiotropy analysis instead of individual trait analysis. [1][2][3][4][5][6][7][8][9][10]27,44 Among other merits, the MFLM can handle missing genotype data naturally.…”
Section: Discussionmentioning
confidence: 99%
“…We assume that the m c variants are located with ordered physical positions 0rt c1 o?ot cmc . To make the notation simpler, we normalized the region ½t c1 ; t cmc to be [0,1]. For the i-th individual in the c-th study, let y cij denote her/his j-th quantitative trait (j = 1,2,⋯,J), G ci ¼ ðx ci ðt c1 Þ; ?…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations